Narratives of Islamic legal theory - Ahmed, Rumee. (Oxford)
x, 176 sayfa
Keywords: “In the critical period when Islamic law first developed, a new breed of jurists developed a genre of legal theory treatises to explore how the fundamental moral teachings of Islam might operate as a legal system. Seemingly rhetorical and formulaic, these manuals have long been overlooked for the insight they offer into the early formation of Islamic conceptions of law and its role in social life. In this book, Rumee Ahmed shatters the prevailing misconceptions of the purpose and form of the Islamic legal treatise. Ahmed describes how Muslim jurists used the genre of legal theory to argue for individualized, highly creative narratives about the application of Islamic law while demonstrating loyalty to inherited principles and general prohibitions. These narratives are revealed through careful attention to the nuanced way in which legal theorists defined terms and concepts particular to the legal theory genre, and developed pictures of multiple worlds in which Islamic law should ideally function. Ahmed takes the reader into the logic of Islamic legal theory to uncover diverse conceptions of law and legal application in the Islamic tradition, clarifying and making accessible the sometimes obscure legal theories of central figures in the history of Islamic law. The book offers important insights about the ways in which legal philosophy and theology mutually influenced premodern jurists as they formulated their respective visions of law, ethics, and theology“ --